STUDY OF SEMIOTICS TOWARD PUNK KIDS T-SHIRT - ratna amalia (Jurnal Sosioteknologi, 2016)
Parental Advisory is the first children's clothing in Bandung which creates t-shirt for kids with punk-styled graphics, typography, and colors. The text of Parental Advisory t-shirt uses negative words. However, it actually has a positive and profound meaning intended for the parents. The consumers considered the dark color tones as unique and unusual. This research become important because children haven't yet understand the meanings of text and images in the t-shirt, and the perception from their surroundings towards dark colors. Although the Parental Advisory is considered negative, but still widely sold in the market. To analyze, this research uses a qualitative-descriptive method, using interviews as main data source. This research needs to uncover the parent's considerations in appreciating text, image, and color in Parental Advisory children t-shirt, and explained the meaning based on study of Semiotics. Based on Barthes's study of Semiotics, psychological effects caused from Parental Advisory Children T-Shirt is one of purchased reason. The meaning of signs in the Parental Advisory from the connotative and denotative aspect has proven to enclose some myth; modern myth, and self-actualization. These myths occur from the dominant English language used in the texts, offensive words, and images that identic with violence. There are also masculinity myths derived from the darker t-shirt tones. Those meanings are constructed myths, yet it was entirely believed by the consumers and therefore, becomes the primary buying considerationKeyword : Semiotic, Children t-shirt, Punk.